Pengaruh Literasi Digital Terhadap Karakter Kritis Siswa Dalam Pembelajaran Ilmu Pengetahuan Sosial - Hikmah Alfiah (Journal of Educational Research and Learning Analytics, 2025)
This study systematically synthesizes empirical evidence on how digital literacy shapes students’ critical character in social studies learning. Using a Systematic Literature Review combined with qualitative meta-synthesis, articles indexed in Scopus and Web of Science from 2018–2025 were selected based on explicit analysis of digital literacy, critical thinking indicators, and social studies or citizenship education. The review identifies a positive and significant effect of digital literacy on critical character, driven particularly by the critical dimension of digital literacy, which enables students to evaluate information credibility, make ethical decisions, and resist disinformation. Critical digital literacy also functions as a mediator that mitigates negative impacts of advanced technologies, including AI-generated content, on critical thinking skills. The findings support the integration of Critical Media Literacy and critical pedagogy into social studies curricula and highlight the need for psychometrically robust instruments (Rasch, PCM) to measure digital literacy and critical thinking in the Indonesian context.